Local Knowledge When Ranking Journals: Reproductive Effects and Resistant Possibilities - Canagarajah, Suresh (Education Policy Analysis Archives, 2014)
This article is based on the engagement of a US-based scholar and faculty members in a non-Western university in a mentoring exercise on publishing. It demonstrates how the “list” constructed in a particular academic department in the university for ranking relevant journals for publication has reproductive effects on knowledge construction. The ranking of journals shapes scholarly interactions both inside and outside the academic department, offering limited possibilities for developing local knowledge. A micro-level orientation to publishing is first adopted to bring out how rhetorical and textual choices are influenced by the list of ranked journals. Next, a broad lens perspective is adopted to explore how academic interactions and communication among local scholars are also shaped by such productivity targets to reproduce dominant knowledge. In the final section, the article reports on the way mentoring was reconfigured to identify strategic textual spaces for representing local knowledge within existing publishing conventions.